KEBEBASAN WANITA PADA TEKS âWARDAH AL-HÄNÄªâ(1908) DALAM ANTOLOGI CERPEN âAL-ARWÄH AL-MUTAMARRIDAHâ KARYA JUBRÄN KHALÄªL JUBRÄN (KAJIAN SOSIOLOGI SASTRA) - Tri Yanti Nurul Hidayati, Mufidah Nuruddiniyah (Jurnal CMES, 2017)
Women and emancipation are two things that can not be separated, both are like two sidesÂ  of the same coin. One form of womens emancipation is a freedom of determining a spouse. This research aims to describe the several forms of womens freedom of determining a spouse in short story of Kahlil Gibran entitled Wardah Al HÄnÄ« based on literary sociology theory of Rene Wellek and Austin Warren. The methodology used to realize that aim is descriptive qualitative. The results reveal that womens freedom of determining a spouse is divided into two perspectives, one relates to the opinion of the character in a story and other determined by his behaviors. In the first side, the character has an opinion that the real happiness in the life only can be brought by love. So, she must choose the man she loved. And in another side, the womens freedom is shown by the way she left her legal husband and went to the other beloved man to make her happiness life.Â